Scoping Review: Pemetaan Model Pelatihan Profesional Digital untuk Guru Pendidikan Jasmani - Abduh Rohmani; Bambang Abduljabar; Cica Yulia; Nandang Rusmana; Maulia Depriya Kembara (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The study aims to identify and classify digital professional training models used for Physical Education (PJOK) educators. This study follows the framework formulated by Arksey & O'Malley and Levac et al., and is structured based on PRISMA-ScR provisions. A literature search was conducted through the Scopus database for the period 2020-2025 by utilizing a combination of keywords related to sports, teacher professional development, and digital technology. Article selection included the removal of duplicates, title and abstract checks, and full-text reading. Data collection was carried out using a standardized charting form. From 18 articles that met the criteria, it was revealed that technologies such as VR/AR, wearable devices, motion sensors, gamification, and online learning platforms can improve the quality of teaching practices and several aspects of learning outcomes, requiring collaboration with teachers, and equipped with ongoing training and technical support. Most studies still face limitations in the form of quasi-experimental designs, small sample sizes, short intervention durations, reliance on self-reports, and minimal long-term measurements. Challenges in implementation were also identified, such as varying levels of teacher digital readiness and lack of infrastructure. This study demonstrates that digital professional training has significant potential to support changes in learning. Further research is needed to strengthen policies and formulate effective and sustainable models. Keywords: Digital Training, Physical Education, Teacher Professional Development